The Effectiveness of Elsa Speak to Improve Speaking Skill in Extra Class Ma Al-Bairuny - Sa'diyah, Lailatus; Bahtiar, Yuyun; Nur, Luluk Choirun Nisak; Afidah, Nurul; Ma'arif, Iin Baroroh (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This research aimed to examine the effectiveness of the Elsa Speak application as a learning media to improve students’ English-speaking skills in the extra class at MA Al-Bairuny. The research used a quasi-experimental design with two groups: an experimental group taught using the AI-based Elsa Speak application, and a control group taught without the application. The research began with a pre-test to assess students’ speaking abilities. The average pre-test score of the experimental group was 57.33, while the control group had an average of 61.67. During the treatment, the experimental group practiced speaking using Elsa Speak, which offers features such as pronunciation analysis and instant feedback. The control group continued learning through traditional methods without the application. After the treatment, a post-test was conducted. The experimental group showed significant improvement with an average score of 70.00, increasing by 12.67 points. Meanwhile, the control group showed only slight progress, with an average post-test score of 62.33, an increase of just 0.67 points. The results indicate that Elsa Speak is effective in improving students’ pronunciation, fluency, and confidence. This research highlights the potential of AI-based technology to enhance the quality of English language education in the digital era.